Analiza uporabe aplikacije za sledenje stikov med mladimi - Masnec, Lana (Uporabna informatika (Ljubljana), 2024)
The COVID-19 coronavirus pandemic was seen by many as a major milestone for the mass uptake and use of eHealth services. Contact tracing applications are part of the eHealth services that can make an important contribution to controlling the spread of the disease. These are only effective when a sufficient proportion of the population (56-60%) actually uses them, which was not achieved in European countries at the time of the COVID-19 pandemic. As we can expect the spread of dangerous viruses in the future, it is necessary to understand holistically the drivers of active use and rejection of contact tracing applications. In this article, we examined whether previously known factors influencing the intention to use also influence the actual use of the application. We focus on young adults aged between 18 and 35. We find that the key factors influencing the actual use of a contact tracing application are perceived ease of use, social influence, perceived usefulness at the personal level, and privacy concerns. However, we have not confirmed the impact on perceived usefulness at the societal level and on trust in technologies.
Keywords: actual use; aplikacija za sledenje stikom; contact tracing application; COVID-19 pandemic; dejanska uporaba; mladi odrasli; pandemija covid-19; privzemanje tehnologij; technology acceptance; young adults